Supervision as the Signature Pedagogy for Counseling Leadership - Melissa Luke; Harvey C. Peters (Teaching and Supervision in Counseling, 2020)
The authors apply the signature pedagogies framework for pedagogical foundations in counselor education put forth by Baltrinic and Wachter Morris (In press) to counseling leadership. Accordingly, we first define counseling leadership and describe the limited literature focused on pedagogical practices related to counseling leadership. Next, we discuss supervision and use the notion of broad and specific features as discussed within Baltrinic and Wachter Morris (In press) to systematically examine whether there is a signature pedagogy for counseling leadership, and purport how supervision of counseling leadership largely fulfills the criteria. Finally, we discuss how supervision of counseling leadership can be utilized and further expanded, followed by a consideration of the subsequent implications for counseling leadership practice and future research.
Keywords: clinical supervision; counselor education; counseling leadership; signature pedagogy; supervision of leadership